Fostering digital competence in pre-service biology teachers - Aidana Aubakir; Assiya Maimatayeva; Makhabbat Amanbayeva; Gani Issayev; Akylbek Meirbekov (International Journal of Evaluation and Research in Education (IJERE), 2026)
Biology teachers are required to use digital technologies in their teaching practice. The issue is that biology students do not receive sufficient training or have access to enough resources to use digital technologies effectively in their studies. The solution to this problem is to develop and implement an effective strategy for enhancing the digital competence of biology teachers. This strategy involves a comprehensive approach that includes pre-test/post-test assessments and targeted training sessions focused on improving digital literacy, communication, and digital content creation. The study employed quantitative research methods, including questionnaires and interviews with students. A total of 100 pre-service biology teachers were recruited from different teacher education universities in Kazakhstan. The results show that the use of innovative teaching practices can enhance the level of digital competence of pre-service biology teachers. The students demonstrated significant improvement across five dimensions of digital competency: information and digital literacy, communication and collaboration, digital content creation, safety, and problem solving. Barriers related to the inclusion of digital technologies into teaching included the inadequate training of teachers, lack of experience, lack of resources, lack of time, and no internet access. The present findings can be used to develop new education programs for teachers and improve the effectiveness of the existing ones.